The Effect of Educational Background and Work Experience on Employee Performance at PT. Raflesia Alam Sejahtera Bengkulu Branch - Shintia Putri Sarmauli Manurung; Ahmad Soleh; Ida Ayu Made Er Meytha Gayatri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Every company needs to pay attention to factors that can affect employee performance, such as educational background and work experience. Employee performance is an action taken by employees in carrying out the work assigned by the company. The purpose of this study is to determine whether educational background and work experience have a significant simultaneous effect on employee performance at PT. Raflesia Alam Sejahtera, Bengkulu Branch. This study is quantitative in nature, using association (intercorrelation) with research based on positivist philosophy to examine a specific population and sample. The data collection method in this study used a questionnaire technique, with a sample of 30 respondents. The results of this study show that the multiple linear regression is Y = -10.820 + 0.686 X1 + 0.547 X2 + 2.620. Where the coefficient has a positive and significant value, it means that there is a positive or unidirectional correlation between the variables of Educational Background (X1) and Work Experience (X2) in determining employee performance. The results of the educational background variable test show that t count 2.710 > t table 1.701 and significance 0.012 < 0.05, so the results of Ha hypothesis are accepted and Ho is rejected, meaning that educational background has a positive and significant effect on employee performance. The results of the work experience variable test show that t count 2.423>t table 1.701 and significance 0.022<0.05, so the results of Ha hypothesis are accepted and Ho is rejected, meaning that work experience has a positive and significant effect on employee performance. Based on a comparison of Fcount value with F table value, the value of Fcount is greater than Ftable, namely 155.025> 3.35, so it can be concluded that the hypothesis is accepted, meaning that there is a simultaneous influence between educational background (X1) and work experience (X2), which significantly contributes to employee performance. This is evident at a significance level of 0.000 < 0.05.